The association between Toxoplasma gondii seropositive status and diabetes mellitus in obese and non-obese subjects in Baghdad - Al-Khafajii, Ghufran Salman; Al-Warid, Harith Saeed; Al-Abbudi, Fadhil A. (Iraqi Journal of Science, 2021)
Anti-Toxoplasma gondii seropositive status among obese and diabetic patients has recently attracted substantial attention. The objective of this study was to assess the seropositive rate of T. gondii and its relation to high body mass index (BMI), diabetes, and metabolic syndrome among participants (n=100) who attended Al-Kadhimiya Teaching Hospital, Baghdad-Iraq. An observational analytical study was conducted from October 2019 to March 2020. Participants were divided into three groups based on their BMI; obese (n=38), overweight (n=32) and normal (n=30). In addition, they were divided into diabetic (n=45) and non-diabetic (n=55) based on clinical examination, laboratory examination, and medical interview. Another classification was considered: Obese-diabetic (n=24), obese- non-diabetic (n=14), overweight-diabetic (n=13), overweight non-diabetic (n=19), normal-diabetic (n=8) and normal-nondiabetic (n=28). Finally, participants were divided into metabolic syndrome-positive (n=64) and metabolic syndrome negative (n=36). Serum samples were taken from all participants and examined for the detection of anti-T.gondii IgG and IgM antibodies. The anti T.gondii IgG positive rate was higher in the “overweight” compared to the “obese” and “normal BMI” groups. No significant differences (P=0.22) in seropositive rate were indicated among groups. The results also showed that there was no significant difference (P=0.84) in anti-T. gondii IgG positive rate between diabetic and non-diabetic patients. While the anti T.gondii IgG was significantly (P=0.03) higher in patients with metabolic syndrome as opposed to those with no metabolic syndrome. The results also showed that normal-diabetic and overweigh-diabetic patients had the highest anti-T.gondii IgG positive rate, although no significant differences were noticed among groups. Some other parameters were also examined for the participants, including abdominal obesity, cholesterol, triglycerides, high density lipoprotein (HDL), very low density lipoprotein (VLDL), glucose and glycated haemoglobin. Significant differences were noticed only for abdominal obesity and HDL (P˂0.05) between anti T.gondii IgG positive cases and anti T.gondii IgG negative cases. Other factors did not show significant differences between these two groups. Finally, this study showed that T. gondii seropositive status played a significant role in changing only HDL level while other parameters of lipid profile were not influenced by T.gondii seropositivity among obese, diabetic patients and metabolic syndrome patients.